2015
DOI: 10.1002/ajhb.22749
|View full text |Cite
|
Sign up to set email alerts
|

Crossing the peninsula: The role of Noh Bec, Yucatán, in ancient Maya Classic Period population dynamics from an analysis of dental morphology and Sr isotopes

Abstract: Dental morphology and (87) Sr/(86) Sr ratios indicate intense population dynamics in the peninsula during the Maya Classic period. Despite the different nature of the dental and isotopic indicators, results agree with archaeological evidence and with proposed trade routes in the peninsula.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 39 publications
(68 reference statements)
0
6
0
Order By: Relevance
“…Through analyses of tooth morphology, Scherer (2007) and Cucina (2015) have demonstrated that the idea of “isolation by distance,” the increase in biological dissimilarity between geographically separated populations (Wright 1943), does not fit with broad affinity patterns in the Maya region. These and other studies suggest there was a large amount of gene flow occurring, particularly during the Classic period (Cucina 2015; Cucina et al 2015; Scherer 2007; Scherer and Wright 2015; Willermet et al 2013). Many studies have contextualized one or more sites within the broader Maya region and found that geographic and temporal clustering do not yield distinctions between major centers (Aubry 2009; Cucina and Tiesler Blos 2004; Cucina et al 2008, 2015; Scherer 2007; Willermet et al 2013).…”
Section: Classic Maya Social Structure and Organization—popular Perceptionsmentioning
confidence: 68%
See 2 more Smart Citations
“…Through analyses of tooth morphology, Scherer (2007) and Cucina (2015) have demonstrated that the idea of “isolation by distance,” the increase in biological dissimilarity between geographically separated populations (Wright 1943), does not fit with broad affinity patterns in the Maya region. These and other studies suggest there was a large amount of gene flow occurring, particularly during the Classic period (Cucina 2015; Cucina et al 2015; Scherer 2007; Scherer and Wright 2015; Willermet et al 2013). Many studies have contextualized one or more sites within the broader Maya region and found that geographic and temporal clustering do not yield distinctions between major centers (Aubry 2009; Cucina and Tiesler Blos 2004; Cucina et al 2008, 2015; Scherer 2007; Willermet et al 2013).…”
Section: Classic Maya Social Structure and Organization—popular Perceptionsmentioning
confidence: 68%
“…These and other studies suggest there was a large amount of gene flow occurring, particularly during the Classic period (Cucina 2015; Cucina et al 2015; Scherer 2007; Scherer and Wright 2015; Willermet et al 2013). Many studies have contextualized one or more sites within the broader Maya region and found that geographic and temporal clustering do not yield distinctions between major centers (Aubry 2009; Cucina and Tiesler Blos 2004; Cucina et al 2008, 2015; Scherer 2007; Willermet et al 2013). For example, using morphometric and strontium data, Scherer and Wright (2015) suggest that Tikal saw an immigration influx during the Early Classic, which resulted in increased phenotypic variation.…”
Section: Classic Maya Social Structure and Organization—popular Perceptionsmentioning
confidence: 68%
See 1 more Smart Citation
“…Morphological analysis in other archaeological areas of the Maya lowlands indicates intense population dynamics during the Classic and Postclassic periods (Cucina 2015). For instance, by analyzing dental traits from many burials of the northern and central Maya lowlands, Cucina (2013) and colleagues (Cucina et al 2015) argue that samples from inland sites of the Maya lowlands, such as Calakmul, Altar de Sacrificios, Ceibal, and Dzibanche, had dental morphological traits that clustered together, suggesting less gene flow with other coastal and northern groups, such as Noh Bec, Kohunlich, Xcambo, Jaina, Mayapan, and Chichen, whose dental traits clustered far from the Pasion area.…”
Section: Discussionmentioning
confidence: 99%
“…Although the dental traits support the idea that Ceibal was interacting with non-local groups during the Classic period, the origins of those migrants are not knowable from the current data. Nevertheless, the dental analysis described above implies that, if there were migrants at Ceibal, their origins are probably not in the northern Maya lowlands (Cucina 2015) or Belize (Wrobel 2003).…”
Section: Discussionmentioning
confidence: 99%